The city that became safe New York's lessons for urban crime and its control - Zimring, Franklin E. (New York ; Oxford : Oxford University Press, 2011)
An investigation into the reasons why New York City saw a dramatic drop in crime during the late 20th century into the 21st. Franklin Zimring provides a detailed and comprehensive statistical investigation into the city's falling crime rates.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Crime prevention -- New York (State) -- New York; Crime -- New York (State) -- New York; Police -- New York (State) -- New York